Do You Speak Dialect? Yes! - Kardelis, Vytautas; Forgeron, Gabriela (Lietuvių kalba, 2024)
This article constitutes a continuation of the publication ‘Measuring Pronunciation: A Discursive Research Model’ (Kardelis, 2023).The primary objective of the paper was to apply the discourse model of dialectality measurement and to assess its implementation of the behavioural dimension of the trinomial model of language attitudes. The objective of the study was to empirically examine speakers’ attitudes towards the utilisation of dialectal language in informal settings with family members and friends from their native land. To this end, two tasks were identified: firstly, to present the course of the research and discuss the results, and secondly, to outline the research perspectives. The methodological principle of the study was the link between the cognitive and the emotional ↔ behavioural dimension. In essence, the methodology involved a dual-faceted approach: first, to ascertain whether informants employed dialectal language in informal settings with family members and friends from their country of origin; and second, to examine the practical implementation of this linguistic phenomenon. The most significant finding of this study is that the proposed discursive model of dialect measurement research functions in principle, yet it remains to be refined. The study also demonstrates the feasibility of collecting data for the model remotely. Secondly, the study yielded noteworthy insights concerning the utilisation of questionnaires in survey research. The study demonstrates that questionnaires alone cannot be relied upon to explain dialect. This is evidenced by the finding that respondents’ self-reported dialect use, in terms of its circumstances and frequency, is subject to a conflict between objective and subjective dialect. This conflict cannot be resolved by questionnaires alone and further research is required. The calculation of the dialect index according to the formula developed in this study demonstrated that, with one exception, RAP informants are more ‘dialectal’ than RAU informants with respect to objective dialect. It is important to note that it is not possible to draw any broader generalisations from a selection of several or even a few dozen informants on one or another of the points under study. The snowball method, a favoured approach among sociolinguists and dialectologists, may appear advantageous in terms of material collection. However, it is crucial to recognise its inherent limitations, the most significant of which revolves around its randomness. It is challenging to identify patterns within randomness, particularly when attempting to achieve a comprehensive overview. Consequently, a dilemma arises in the pursuit of an objective portrayal of the dialectal landscape of the Lithuanian language, its characteristics, and the indices that define it. This challenge is not merely a methodological or technical problem, but rather a complex one that demands resolution. A further challenge lies in the monitoring process within the domestic environment, a prerequisite for achieving an objective and reliable measurement of dialectal variation.